2016
DOI: 10.3390/catal6120188
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Morphology Controlled ZnO in Catalysis

Abstract: Zinc oxide (ZnO), with the unique chemical and physical properties of high chemical stability, broad radiation absorption range, high electrochemical coupling coefficient, and high photo-stability, is an attractive multifunctional material which has promoted great interest in many fields. What is more, its properties can be tuned by controllable synthesized morphologies. Therefore, after the success of the abundant morphology controllable synthesis, both the morphology-dependent ZnO properties and their relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 264 publications
(301 reference statements)
2
59
0
Order By: Relevance
“…It seems that Mg-doped ZnO NPs act similar to electron sink, which consequently can enhance significantly the separation of the photo-generated electron−hole pairs and inhibit their recombination resulting in improved photocatalytic activity [58]. …”
Section: Resultsmentioning
confidence: 99%
“…It seems that Mg-doped ZnO NPs act similar to electron sink, which consequently can enhance significantly the separation of the photo-generated electron−hole pairs and inhibit their recombination resulting in improved photocatalytic activity [58]. …”
Section: Resultsmentioning
confidence: 99%
“…The smaller Pd nanoparticles are expected to result in broad peaks and the correspondingly low signal from the particles [24]. The Pd nanoparticles of comparable dimensions (4-6 nm) were also not observed over the ZnO support in powder X-ray The nitrogen physisorption study demonstrated low surface area of the support of 0.5 m 2 g −1 , which is typical for crystalline ZnO materials [42,43]. The powder X-ray diffraction study showed mainly the presence of hexagonal wurtzite crystals with the average diameter of 60 nm based on the Scherrer equation estimation for the most intensive peak at 2θ = 37.4 • (Figure 2).…”
Section: Characterisationmentioning
confidence: 99%
“…The macroporous structure formed by such needle-shaped crystals of the coating is greatly beneficial for the internal mass transfer as it provides high diffusion coefficients when compared to microporous materials. The nitrogen physisorption study demonstrated low surface area of the support of 0.5 m 2 g −1 , which is typical for crystalline ZnO materials [42,43]. The powder X-ray diffraction study showed mainly the presence of hexagonal wurtzite crystals with the average diameter of 60 nm based on the Scherrer equation estimation for the most intensive peak at 2θ = 37.4° (Figure 2).…”
Section: Characterisationmentioning
confidence: 99%
“…ZnO in a nanosized form is an indispensable candidate for electronic, optical, and gas sensors, as well as in catalysis applications, owing to its band gap value of 3.37 eV, large exciton binding energy of 60 meV and high electron mobility [1][2][3][4][5]. In the last decade, ZnO with various morphologies, including flower-like [6,7], nanodisc [1], nanobelt [8], and nanotube [9], targeting various application areas, have been investigated using different synthesis methods, e.g., sol-gel [10], hydrothermal [11], the microwave-assisted method [12] and spray pyrolysis [13].…”
Section: Introductionmentioning
confidence: 99%